Factor associated with health-related quality of life among population in Northern Jordan (Epidemiology, Biostatistics, and Public Health, 2022)
Objective: This study aimed to assess health-related quality of life among Jordanians. Design: A cross-sectional design study was conducted at three shopping centers in Northern Jordan. Measures: Respondents were invited to fill a questionnaire assessed quality of life (QoL) using the SF-36 health survey.Results: Data was obtained from 915 Jordanian adults from the public with a mean age of 33.8 years (SD= 28.2). The total SF-36 score for the whole population was 71.2. Significantly, females reported lower SF-36 scores in both physical and emotional health domains (P=